Depiction of Shona marriage institution in Zimbabwe local television drama, Wenera Diamonds. - Samanga, T.; Matiza, Vimbai M. (Bindura University Press, 2022)
Marriage is a highly celebrated phenomenon among the African people. It is one of the important institutions among the Shona and Ndebele people in Zimbabwe as expressed in the saying ‘musha mukadzi’ and ‘umuzingumama’ (home is made by a woman) respectively. However with the coming of colonialism in Zimbabwe, marriage was not given the appropriate respect it deserves. This has given impetus to this paper where the researchers in the study through drama want to bring out the depiction of marriage institution in a post -independence television drama, Wenera Diamonds (2017). This paper therefore, aims to show the impact of neo-colonialism on Shona marriage institution. The neo colonial period is characterised with the perpetuation of Western imperial interests through protocols of diplomatic relations, treaties and existing bilateral agreements which marked a new phase of relationships with former colonisers. The aim of this article therefore is to depict marriage institution in neo colonial Zimbabwe in Wenera Diamonds (2017), a Zimbabwean television drama. Using qualitative research methodology, the research employs content analysis to elucidate the depiction in the said performance. Guided by the Africana womanist perspective, the article argues that the indigenous knowledge needed for African social development is rendered irrelevant by a dysfunctional set of values of the western hegemony. Against that, the paper establishes that the depiction of marriage institution in Wenera diamonds is a reflection of imperialist colonial forces on the black person hence the need to go back to basics and resuscitate their culture.